Short term results of a single autologous whole blood injection for treatment of resistant tennis elbow - Wani, Mubashir Maqbool; Manzoor, Qazi Waris; Bashir, Arshad; Mir, Bashir Ahmed; Wani, Suhail (International Journal of Research in Orthopaedics, 2020)
Background: Lateral epicondylitis commonly called tennis elbow is a common cause of elbow pain and involves degeneration of common extensor origin with no unanimously supported algorithm for the treatment. Recently, autologous blood injection has been reported for the treatment of resistant cases. We present the short term results of a single shot of autologous whole blood for the treatment of resistant tennis elbow. Methods: The study was conducted on 56 patients who fulfilled the other inclusion criteria’s. 2 ml of autologous whole blood was introduced just proximal to the lateral epicondyle and the contents were injected on the under surface of the extensor carpi radialis group of muscles. Pain severity using VAS and Nirschl Staging was assessed before injection and re-evaluation was done at 4 weeks, 12 weeks and 6 months. Results: Before the procedure average pain score was 7.5(range 5-9). The average Nirschl stage was 5.5 (range 4-7). After autologous blood injections the average pain score decreased to 4 at 4 weeks, 2.8 at 12 weeks and 2.5 at 6 months. The average Nirschl stage decreased to 3.53 at 4 weeks, 2.45 at 12 weeks and 2.3 at 6months. The reduction was statistically significant (p<0.001). 28 out of 56 patients (50%) were completely relieved of pain with a pain score of 0 at 6 months. There was no major complication. Conclusions: A single injection of autologous whole blood for resistant tennis elbow is an economical and effective treatment and has an excellent safety profile.